PELAKSANAAN PEMBELAJARAN SEKOLAH INKLUSIF KELAS I SD ST. AGATHA PALEMBANG - Restu Paulina S (Universitas Katolik Musi Charitas, 2020)
The purpose of this research is to describe the implementation of inclusive school learning in SD St. Agatha Palembang in terms of education management, curriculum management, inclusive school learning models, education management, facilities and infrastructure management, financing management, school relations management with the community. This research uses a descriptive qualitative approach. Data collection techniques with interviews, questionnaires, and documentation. Data validity is done by triangulation. Data analysis techniques using interactive models from Miles and Huberman. The results of the study: (1) acceptance of new students does not distinguish between students with special needs and regular students, student identification is done simply, (2) the curriculum used is modified by adding a number of subjects, (3) a full inclusive class model, (4) do not use the help of special assistant teacher, psychology, and SLB teachers in its implementation, (5) do not provide special facilities and infrastructure for students with special needs, (6) do not distinguish funding, (7) supporting factors: the relationship between schools and the community is established with good, inhibiting factor: some people feel strange ABK attend school in regular schools.